PENGARUH KONEKSI POLITIK, STRUKTUR KEPEMILIKAN DAN FAKTOR LAINNYA TERHADAP PRAKTIK MANAJEMEN LABA - Noviana Chandra; Ricky A. Mulyana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to examine the effect of political connections, managerial ownership, institutional ownership, audit quality, return on asset, debt to equity, sales growth, and board size on earnings management practices. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. The sample consists of 95 manufacturing companies with a total of 285 data were selected using purposive sampling method. The results showed that debt to equity has a negative effect on earnings management. In addition, political connections, managerial ownership, institutional ownership, audit quality, return on asset, sales growth, and board size do not have a significant effect on earnings management.